Building Occupational Health and Safety Culture for the RSG-GAS Nuclear Facility at BRIN Serpong - Umi Rusilowati; Hamsinah B.; Ridwan Taufik Hidayat; Taswanda Taryo (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2026)
The 30 MW G.A. Siwabessy Multipurpose Reactor Facility (RSG-GAS) at BRIN Serpong is used for research, isotope production, and nuclear technology development and occupational health and safety (OHS) is a very important aspect of the facility. Although there has never been a nuclear accident at the RSG-GAS nuclear facility, to anticipate this, the first study on the possibility of employees making errors at the RSG-GAS facility has been conducted. The aim of this research is to analyze the effectiveness of health, safety and culture of employees working at the Safety division of the reactor RSG-GAS. A mixed method approach with two main perspectives of the workforce and the Institution has been carried out. Data collection and empirical facts that demonstrate the urgency of implementing an OHS/K3 system have been implemented using mix-method. A study of workers' awareness, compliance, and perceptions of OHS implementation, including the application of SOPs in daily operations, was conducted. The results indicate that the effectiveness of OHS implementation at the RSG-GAS BRIN Serpong facility is currently mostly supported by the strength of the regulatory system. The OHS implementation going forward depends not only on adding regulations or improving safety technology, but also on strengthening safety culture consistent training, and a focused, sustainable management commitment. The good implementation of OHS at RGS-GAS BRIN Serpong then makes Indonesia a pioneer in implementing OHS, especially in ASEAN, because the RSG-GAS Reactor is currently the largest nuclear reactor in the Region.